Predictors of mortality and ICU requirement in hospitalized COVID‐19 patients with diabetes: A multicentre study - Md Asaduzzaman; Mohammad Romel Bhuia; Mohammad Zabed Jillul Bari; Zhm Nazmul Alam; Khalidur Rahman; Enayet Hossain; Munsi Mohammad Jahangir Alam (Wiley, 2023)
Abstract Aim This study aimed to identify the predictors of mortality and ICU requirements in hospitalized COVID‐19 Patients with Diabetes. Design Cross‐sectional study. Methods It was a retrospective study of patients hospitalized with COVID‐19 infection from October 2020-February 2021 in four hospitals in Sylhet, Bangladesh. Logistic regression analysis was applied to explore the predictors of ICU requirement and in‐hospital mortality. Results In the whole cohort (n = 500), 11% of patients died and 24% of patients required intensive care unit (ICU) support. Non‐survivors had significantly higher prevalence of lymphopenia, thrombocytopenia and leukocytosis. Significant predictors of in‐hospital mortality were older age, neutrophil count, platelet count and admission peripheral capillary oxygen saturation (SpO2). Older age, ischemic heart disease, WBC count, D‐dimer and admission SpO2 were identified as significant predictors for ICU requirement. Patient or Public Contribution No.